Culture and Urban Development (The Case of Pecs) - Horváth, Gyula (Discussion Papers, 1992)
The longer term future image of Pécs makes it very important to examine the cultural resources of the city from the viewpoint of urban development as well. A number of examples of revitalization of depression areas in developed countries prove that the intellectual life, culture, cultural services mean important forces in urban development, and take part in the reorganization of the socio-economic structure of the city in economic crisis as pulling sectors. The triple urban development function of cultural sectors (value transmitters, value producers, attractors of capital) has not yet been taken into account in Hungarian settlement policy. Culture, as economic sector, has been approached with the traditional fiscal attitude, thus the above complexity has not been realized in urban development. It can be an important new model if a city can base its cultural development on the above approach, i.e. the direct and indirect impacts of culture on the economic structure can be demonstrated in a wider social and economic environment, and if new objective needs for the expansion of cultural services can be revealed.